Associations of polymorphisms in the gene promoters of cytokines and matrix metalloproteinases with bone mineral density in postmenopausal type 2 diabetic women - Olga N. Fazullina (Endocrinology Research Centre, 2018)
Background. Osteoporosis and type 2 diabetes are common comorbidities in postmenopausal women. An important role in the bone remodeling over the menopausal transition can be played by cytokines and matrix metalloproteinases (MMPs). It was shown that allelic variants in polymorphic positions of the genes of cytokines and MMPs affect the expression of these molecules under normal and pathological conditions. Aims. To examine associations between polymorphisms in the gene promoters of cytokines (TNFA, IL1B, IL4, IL6, IL10, VEGFA) and MMPs (MMP2, MMP3, MMP9) with bone mineral density (BMD) in postmenopausal women with type 2 diabetes. Materials and methods. We studied 197 Caucasian diabetic women, from 50 to70 years of age. An examination of BMD in the spine, proximal femur and forearm was performed by DEXA. Thirteen polymorphisms in the promoters of TNFA: -238 A/G (rs361525), -308 A/G(rs1800629) and -863 C/A (rs1800630), IL1B: -31 C/T (rs1143627), IL4: -590 C/T (rs2243250), IL6: -174 C/G (rs1800795), IL10: -592 C/A (rs1800872) and -1082 A/G (rs1800896), VEGFA: -2578 C/A (rs699947) and +936 C/T (rs3025039), MMP2: -1306 C/T (rs243865), MMP3: -1171 5A/6A (rs3025058) and MMP9: -1562 C/T (rs3918242), were investigated. Results. Seventy-three women had normal BMD, in 90 ones we revealed osteopenia, and 34 women had osteoporosis. Age, BMI and smoking were strongest predictors of BMD in multivariate regression analysis (p<0.0001, p=0.003 and p=0.01, respectively). In the additive model, C allele and CC genotype in MMP9 -1562 position were associated with low BMD (OR 2.16, p=0.0007 and OR 2.02, p=0.0008, respectively). Association of the polymorphism with BMD remained significant after adjustment for clinical risk factors (p<0.001). Twelve combinations of genotypes, associated positively with low BMD, were revealed by bioinformatic analysis (all p<0.005). The СС genotype in position -1562 of MMP9, CC genotype in position -863 of TNFA, GG genotype in position -308 of TNFA, and AA genotype in position -1082 of IL10 were the most prevalent variants in these combinations. Conclusions. Variability in the gene promoters of cytokines and MMPs may confer individual susceptibility to osteoporosis in postmenopausal type 2 diabetic women.